Differential effects of bilingualism and culture on early attention: a longitudinal study in the U.S., Argentina, and Vietnam - Tran, Crystal D.; Arredondo, Maria M.; Yoshida, Hanako (Frontiers in Psychology, 2015)
A large body of literature suggests that bilingualism strongly influences attentional processes among a variety of age groups. Increasing studies, however, indicate that culture may also have measurable effects on attentional processes. Bilinguals are often exposed to multiple cultural backgrounds, therefore, it is unclear if being exposed to multiple languages and culture together influence attentional processes, or if the effect themselves are uniquely linked to different attentional processes. The present study explores the relevancy of different attentional processes—alerting, orienting, and executive control—to language and to culture. In the present study, 97 three-year-old (Mean age = 38.78 months) monolingual and bilingual children from three countries (the United States, Argentina, and Vietnam) were longitudinally tested for a total of 5 time points on a commonly used non-linguistic attentional paradigm—the Attention Network Test (ANT). Results demonstrate that when other factors are controlled (e.g., socioeconomic status, vocabulary knowledge, age), culture plays an important role on the development of the alerting and executive control attentional network, while language status was only significant on the executive control attentional network. The present study indicates that culture may interact with bilingualism to further explain previous reported advantages, as well as elucidate the increasing disparity surrounding cognitive advantages in bilingual literature.